(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aimed to explore the role of supply chain management in achieving sustainability in the Kingdom of Saudi Arabia, where the focus was on analyzing how to improve environmental, social and economic efficiency through the application of sustainable supply chain management practices. The study was conducted using a sample of 170 participants from various sectors in the Kingdom, with the aim of collecting and analyzing data to determine the relationship between supply chain management and achieving sustainability. The results showed that there is a strong positive impact of supply chain management on achieving sustainability, as it was shown that adopting sustainable practices can lead to improved environmental performance, reduce operational costs, and enhance the public image of companies. Based on these results, the study recommends the need to enhance awareness of the importance of sustainable supply chain management, adopt sustainability-focused strategies as part of companies’ operational plans, in addition to providing the necessary support and training to employees to ensure that these practices are applied effectively.